Novel super-reduced, pedagogical model for scoping net zero buildings. (15th January 2022) - Fosas, Daniel; Mitchell, Rachel; Nikolaidou, Elli; Roberts, Matthew; Allen, Stephen; Walker, Ian; Coley, David
Abstract: Since early-stage decisions have the largest impact on climate related emissions, if modelling is to help deliver zero carbon designs, tools are needed that can be used by those involved at this stage. By contrast, tools that require a detailed description of the building or a specialist have less usefulness at this point in the design cycle. So, just how simple can models be (mathematically and interface-wise), to give meaningful answers to decisions such as the shape of the building and the glazing ratio? The ideal tool would be pedagogical and leave the user with knowledge that they could apply even earlier to the next project. In this work we present ZEBRA, a highly simplified, quick-to-use, model for scoping zero-carbon buildings. The model only requires approximately 33 inputs, no training, considers embodied emissions and renewables and leaves the user upskilled on zero carbon design. The predictions from 5 very low energy buildings placed into 559 climates obtained by this new model are compared to the leading model for high-performing buildings. The average difference was 0.9 kWh·m −2 ·a −1 (SD = 0.6). The mean time taken to model a building by someone not previously exposed to ZEBRA was 35 min (SD = 8), and 17 min (SD = 3) on second use. Therefore, ZEBRA is highly accurate when compared to the best-in-class tool and can be used quickly by the uninitiated. Hence ZEBRA has the potential to be highly useful as a first-pass tool whilst simultaneously rapidly upskilling the industry. Highlights: New early-stage pedagogical energy/carbon modelling tool developed. Its results are very close to standard industry models, but with very few inputs. On first use, modelling a building typically takes less than 35 min. The approach encourages modelling at an early stage for greatest impact on design. The tool addresses knowledge gaps of architects and the shortage of modellers.